Teachers' belief and use of interactive whiteboards for teaching and learning - Türel, Yalin Kiliç; Johnson, Tristan E. (International Forum of Educational Technology and Society,National Taiwan Normal University, 2012)
Interactive whiteboards (IWB) are regarded as one of the most revolutionary instructional technologies for various educational levels. While the impacts of IWBs in classroom settings have been examined recently in a number of studies, this study not only looks at the perception but also examines the actual usage and behaviors associated with promising IWB features in practical settings. The main goal of this paper is to evaluate both teachers' perceptions and their use of IWBs. A questionnaire was developed based on an extensive literature review as well as related instructional theories and models. The questionnaire consisted of questions about demographics, usage, and teachers' perceptions related to IWBs. For this study, 174 teacher-participants, who have actively used IWBs for instruction, were selected from various educational levels (from grade 6 to 12). The results show that teachers believe that IWBs can be used for different subject domains. Also, teachers believe that IWBs can be used to facilitate learning and instruction under the following conditions, 1) collaboration with colleagues, 2) training about effective instructional strategies using IWB, and 3) more frequent teacher use of IWBs to improve IWB competency. © International Forum of Educational Technology & Society (IFETS).
Keywords: Interactive learning environments; Interactive whiteboard; Interactive whiteboard teacher scale; Secondary education; Technology acceptance model; Technology adoption; Technology integration